2015
DOI: 10.1146/annurev-lawsocsci-120814-121723
|View full text |Cite
|
Sign up to set email alerts
|

Race, Ethnicity, and Culture in Jury Decision Making

Abstract: This article reviews a growing body of social science research indicating that race, ethnicity, and culture can influence the judgments and behaviors of juries. The first section addresses research on jury bias, which shows that jurors often make harsher judgments of defendants from other racial and ethnic groups and are more likely to give death sentences in cases involving Black or Latino defendants and White victims. However, these effects are moderated by several factors related to the trial parties, conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 72 publications
1
43
0
2
Order By: Relevance
“…Interestingly, they found that these discrepancies disappeared if race was made a focal point in the case by adding that the defendant had been the victim of racial slurs. Their findings are representative of the overall findings of a series of studies on the effects of bias in jury proceedings; for an excellent summary see Hunt (, esp. pp.…”
supporting
confidence: 61%
“…Interestingly, they found that these discrepancies disappeared if race was made a focal point in the case by adding that the defendant had been the victim of racial slurs. Their findings are representative of the overall findings of a series of studies on the effects of bias in jury proceedings; for an excellent summary see Hunt (, esp. pp.…”
supporting
confidence: 61%
“…Years of research demonstrate that race influences jurors' perceptions and decisions in cases involving racial minority defendants and victims (for a review, see Hunt, ). White jurors assign more guilt and more punitive sentences to racial minority (Black, Latinx) defendants compared with White defendants (Devine & Caughlin, ; Sweeney & Haney, ; but see Mazzella & Feingold, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Prior studies and meta-analytic reviews suggest a small but "significant" influence of defendant race on jury verdicts generally (Devine & Caughlin 2014;Mitchell et al 2005). In death penalty cases, victim race often has a stronger influence, while in noncapital cases, the focus is on the defendant (Hunt 2005). Research also suggests that stereotyping can affect some jurors' decision making (Johnson et al 1995;Jones 1997;Mitchell et al 2005).…”
Section: Iia Study Overviewmentioning
confidence: 99%
“…The crime type, along with accompanying system and estimator variables, may affect the accuracy of an eyewitness. Some studies suggest that seriousness of the crime matters, such as in death penalty cases (Hunt 2005). Accordingly, we included two crime types (sexual assault, burglary) in our designed study.…”
Section: Iia Study Overviewmentioning
confidence: 99%